Defective Viral Genomes: Critical Danger Signals of Viral Infections - López, Carolina B. (American Society for Microbiology, 2014)
Viruses efficiently block the host antiviral response in order to replicate and spread before host intervention. The mechanism initiating antiviral immunity during stealth viral replication is unknown, but recent data demonstrate that defective viral genomes generated at peak virus replication are critical for this process in vivo. This article summarizes the supporting evidence and highlights gaps in our understanding of the mechanisms and impact of immunostimulatory defective viral genomes generated during natural infections.